Hight return-to-sport rate following traumatic spine injury in amateur athletes - Philipp Raisch; Tabea Hirth; Michael Kreinest; Sven Y. Vetter; Paul A. Grützner; Matthias K. Jung (BMC, 2024)
Abstract Introduction Data on the resumption of sporting activity (return-to-sport, RTS) after traumatic spine injuries are mainly available for elite athletes. This study aimed to determine the RTS rate in amateurs after spine injury and to identify factors possibly influencing RTS. Methods First, a retrospective analysis of clinical data of patients with traumatic spine injuries receiving inpatient treatment at a national trauma center from 2016 to 2020 was performed. Patients up to the age of 60 who were active in sports before the injury were included. Patients with the following relevant concomitant injuries were excluded: spinal cord injury, pelvic injury, extremity injuries, as well as craniocerebral trauma grade 2 or higher. A telephone interview on participants' RTS within the first year after the injury was conducted. Participants with early and those with late or no RTS were compared in univariate analysis regarding potential influencing factors. The level of significance was set to p < .05. Results Thirty-seven women (39%) and 57 men (61%) were included. The mean age was 44 years (16-60). The numbers of patients per injured segment of the spine were: cervical 15 (16%), thoracic 28 (30%), lumbar 33 (35%), multiple spine segments 18 (19%). Thirty patients (32%) were treated conservatively and 64 (68%) surgically. The RTS rate after six months was 62%, corresponding to 57 patients. Compared to patients with late or no RTS, patients with RTS within six months had a significantly lower BMI (24.6 vs. 27.4 kg/qm, p = .004), had isolated cervical spine injuries significantly more often (24% vs. 6%, p = .020), and had undergone outpatient or inpatient rehabilitation significantly less often (35% vs. 72%, p < .001). There were non-significant trends regarding mean age (42 vs. 46 years, p = .175), surgical therapy (66% vs. 75%, p = .333), and the proportion of patients who, before the injury, had been physically active for at least five hours per week (50% vs. 33%, p = .113). Patients with RTS within six months had sustained their spinal injury in a sports accident twice as often (28% vs. 14%, p = .121). Gender, preexisting medical or spinal conditions, severe injuries (types A4, B or C according to AO Spine), and surgical therapy were not significantly associated with RTS. The RTS rate within twelve months was 81% (76 patients). Conclusion The RTS rate in amateur athletes after an isolated spinal injury without spinal cord injury was high, with 62% after six and 81% after twelve months. This reflects the effectiveness of the existing treatment and posttreatment concepts. Normal-weight patients and isolated cervical injury are favorable factors for RTS. The use of inpatient rehabilitation as a marker of protracted healing is associated with delayed or no RTS.